Differential involvement of cAMP/PKA-, PLC/PKC- and Ca2+/calmodulin-dependent pathways in GnRH-induced prolactin secretion and gene expression in grass carp pituitary cells - Li, Wensheng; Ye, Cheng; He, Mulan; Ko, Wendy K. W.; Cheng, Christopher H. K.; Chan, Ying Wai; Wong, Anderson O. L. (Frontiers in Endocrinology, 2024)
Gonadotropin-releasing hormone (GnRH) is a key stimulator for gonadotropin secretion in the pituitary and its pivotal role in reproduction is well conserved in vertebrates. In fish models, GnRH can also induce prolactin (PRL) release but little is known for the corresponding effect on PRL gene expression as well as the post-receptor signalling involved. Using grass carp as a model, the functional role of GnRH and its underlying signal transduction for PRL regulation were examined at the pituitary level. Using laser capture microdissection coupled with RT-PCR, GnRH receptor expression could be located in carp lactotrophs. In primary cell culture prepared from grass carp pituitaries, the native forms of GnRH, GnRH2 and GnRH3, as well as the GnRH agonist [D-Arg6, Pro9, NEt]-sGnRH were all effective in elevating PRL secretion, PRL mRNA level, PRL cell content and total production. In pituitary cells prepared from the rostral pars distalis, the region in the carp pituitary enriched with lactotrophs, GnRH not only increased cAMP synthesis with parallel CREB phosphorylation and nuclear translocation but also induced rapid rise in cytosolic Ca2+ by Ca2+ influx via L-type voltage-sensitive Ca2+ channel (VSCC) with subsequent CaM expression and NFAT2 dephosphorylation. In carp pituitary cells prepared from whole pituitaries, GnRH-induced PRL secretion was reduced/negated by inhibiting cAMP/PKA, PLC/PKC and Ca2+/CaM/CaMK-II pathways but not the signalling events via IP3 and CaN/NFAT. The corresponding effect on PRL mRNA expression, however, was blocked by inhibiting cAMP/PKA/CREB/CBP and Ca2+/CaM/CaN/NFAT2 signalling but not PLC/IP3/ PKC pathway. At pituitary cell level, activation of cAMP/PKA pathway could also induce CaM expression and Ca2+ influx via VSCC with parallel rises in PRL release and gene expression in a Ca2+/CaM-dependent manner. These findings, as a whole, suggest that the cAMP/PKA-, PLC/PKC- and Ca2+/CaM-dependent cascades are differentially involved in GnRH-induced PRL secretion and PRL transcript expression in carp lactotrophs. During the process, a functional crosstalk between the cAMP/PKA- and Ca2+/CaM-dependent pathways may occur with PRL release linked with CaMK-II and PKC activation and PRL gene transcription caused by nuclear action of CREB/CBP and CaN/NFAT2 signalling.